2018
DOI: 10.3389/fmicb.2018.01676
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure, Antimicrobial Resistance, and Virulence-Associated Genes in Campylobacter jejuni Isolated From Three Ecological Niches: Gastroenteritis Patients, Broilers, and Wild Birds

Abstract: Campylobacter jejuni is the causal agent of the food-borne infection with the highest incidence in Europe. Both poultry and wild birds are a major reservoir. To gain insight into the population structure, virulence potential, and antimicrobial resistance (AMR), a collection of 150 isolates from three different ecological niches (broilers, wild birds, and human patients) was studied. Despite the high genetic diversity found, the population structure defined two distinct clusters, one formed mostly by broiler an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 61 publications
5
39
1
Order By: Relevance
“…Regarding the genes cdt coding for synthesis and deliver of the cytolethal distending toxin, our findings are similar with those reported by Bang et al [20], Datta et al [43] and Al-Mahmeed et al [44]. In our knowledge, activity of CDT toxin (consisting CDTA, CDTB and CDTC) lead to increase of intestinal epithelial cell volume by stopping cell division cycle at G2 step causing cell destruction [38,[45][46]. Indeed, after adhesion to fibronectin, C. jejuni colonizes intestinal cells and then invasion occurs simultaneously with production of CDT toxin causing inflammatorytype diarrhea in the host organism [47].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding the genes cdt coding for synthesis and deliver of the cytolethal distending toxin, our findings are similar with those reported by Bang et al [20], Datta et al [43] and Al-Mahmeed et al [44]. In our knowledge, activity of CDT toxin (consisting CDTA, CDTB and CDTC) lead to increase of intestinal epithelial cell volume by stopping cell division cycle at G2 step causing cell destruction [38,[45][46]. Indeed, after adhesion to fibronectin, C. jejuni colonizes intestinal cells and then invasion occurs simultaneously with production of CDT toxin causing inflammatorytype diarrhea in the host organism [47].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, virulence genes cadF and cdtA were detected in all tested strains while, cdtB, and cdtC were isolated in 89.51% and 90.32% respectively in these isolates. This high prevalence of these four (4) genes isin agreement with several studies that found it in nearly all of theCampylobacterisolates [1,38]. The cadF gene is coding for a putative OmpA-like protein that mediates bacterial adhesion by binding to host fibronectin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The C. jejuni strain collection, previously described [15], is composed of 150 isolates obtained from faeces of three different sources: human patients suffering from symptomatic gastroenteritis (50 isolates), broiler chickens (50 isolates), and wild birds (50 isolates). Human isolates were obtained from the Santa Creu i Sant Pau Hospital (Barcelona) strain collection.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…Both species have been associated with gastroenteritis in humans, therefore, it was expected the presence of putative virulence genes. On the contrary, it is possible that negative results for the other tested genes were due to differences in DNA sequences of those genes among strains because the primers have been designed on the basis of the representative strains C. jejuni 81-176 and A. butzleri RM4018 (Levican et al 2013, Iglesias-Torrens et al 2018. In this regard, Iglesias-Torrens et al (2018) have observed a higher diversity of cdtA alleles among C. jejuni strains found in wild birds compared to broilers or humans.…”
Section: Discussionmentioning
confidence: 99%